2019
DOI: 10.1177/0300060519881016
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effect of overusing thumbs on smartphone games

Abstract: Objective To assess the impact of repetitive movements of the thumb caused by playing a smartphone game continuously for 30 min. Methods This study recruited healthy volunteers. They were instructed to play a game called Subway Surfers, which ran continuously. Subjects played the game for 30 min. The function of the abductor pollicis brevis and extensor pollicis brevis muscles was assessed by surface electromyography and the signals were obtained at 10 min, 20 min and 30 min. The median frequency (MDF) was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…The dominant population in eleven out of 16 included studies, were school aged kids and young adults aged between 5 to 20 years. Studies were mainly cross sectional, with the exception of one experimental study [ 26 ]. Out of the four possible video gaming devices (computers, consoles, handhelds, smartphones), seven studies included one device [ 25 , 26 , 33 37 ], three studies included two devices [ 38 40 ] and six studies included three or more devices [ 41 – 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dominant population in eleven out of 16 included studies, were school aged kids and young adults aged between 5 to 20 years. Studies were mainly cross sectional, with the exception of one experimental study [ 26 ]. Out of the four possible video gaming devices (computers, consoles, handhelds, smartphones), seven studies included one device [ 25 , 26 , 33 37 ], three studies included two devices [ 38 40 ] and six studies included three or more devices [ 41 – 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies were mainly cross sectional, with the exception of one experimental study [ 26 ]. Out of the four possible video gaming devices (computers, consoles, handhelds, smartphones), seven studies included one device [ 25 , 26 , 33 37 ], three studies included two devices [ 38 40 ] and six studies included three or more devices [ 41 – 46 ]. Due to insufficient information, it is not possible to rule out that in two studies [ 37 , 39 ] more than the indicated devices were used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies, Vukmir, et al reported that a computer printout, like a brochure, does not help most patient comply with the physician's instructions ( 37 ). Abbott reported that poor understanding of the procedure may result in lack of patient cooperation ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Belching, retching, and coughing were the main manifestations of poor cooperation (9). And the visual analog scale (VAS) was used to measure patients' discomfort during the procedure (30)(31)(32)(33), including the scope passing through the throat, nausea, abdominal pain, and bloating. Patients were asked to rate the severity of their symptoms from "0-10, " with "0" being "I felt absolutely comfortable during the procedure" and "10" being "I was suffering to death during the procedure."…”
Section: Methodsmentioning
confidence: 99%